Cyber HUMINT In Cybersecurity: A Content Analysis - Koivula, Juho Hermanni (2024)
The subject of the study is "cyber HUMINT." HUMINT means human intelligence collected by humans and/or from humans. The cyber prefix in the term "cyber HUMINT" means that it is conducted in cyberspace, an artificial environment. Interconnected systems and networks enable it. The study analyzed the online content of private cybersecurity organizations by answering the question, “What is cyber HUMINT in cybersecurity?” The study uses content analysis and draws on various academic sources to explore how human intelligence works in the traditional and digital era. The research method chosen is qualitative content analysis, a systematic approach to analyzing and interpreting the content of various online content providers' "cyber HUMINT" on cybersecurity. The approach follows the American tradition of grouping similar and disaggregated content to create a hierarchical structure where larger similar groups form a whole. The first subcategory covers techniques to gain insight into the intentions of threat actors and the evolving threat landscape. The second category highlights the importance of proactive cyber intelligence gathering to identify potential cyber threats before they cause damage. The latter highlights the role of "cyber HUMINT" in cyber threat intelligence and emphasizes its importance in forming preventive strategies based on the cyber threat landscape. Overall, this is a proactive approach to human-centered cyber threat intelligence. The study concludes that cyber HUMINT plays a significant role in gathering threat information from human sources to enhance cyber security measures. The study highlighted the human dimension of cybersecurity, cyber intelligence, and operations in cyberspace and the digital world. The study delved into how technology is transforming the method of human intelligence from a cybersecurity perspective. Automation to scale up operations, the ethics of operations, and compliance with the law due to human-centricity emerged as important perspectives.